A Social Life of Pots in Southern Africa. Issue 2 (3rd May 2020) - Riep, David M. M.
Abstract: The movement of objects both within and across contexts often helps to define social relations. This article explores this notion by focusing on five specific examples of pottery production and use in the history of southern Africa, with examples ranging from early Cape colonial coarse earthenware vessels to 19th- and 20th-century pots produced in and around the central interior, and contemporary South African ceramics. By exploring the contextual production and function of such objects, as well as their formal significance and the movement of such objects across cultural and social boundaries, one can see how pottery in southern Africa maintains a central role in the formation and maintenance of cooperative and interdependent relationships.